Catholic churches in the Visayas and the earthquake of 15 October 2013 - Lita, Reynaldo (Philippine studies : historical and ethnographic viewpoints, 2016)
"On 15 October 2013 an earthquake of 7.2 magnitude struck the Central Visayas. It caused huge devastations, reducing to rublle some centuries-old Catholic Churches in Bohol. Past architectural interventions enabled some edifices to survive the quake, but inappropriate additions made quite recently rendered other structures vulnerable to destruction. Partially damaged structures have been undergoing restoration by the National Historical Commission of the Philippines (NHCP). The NHCP's permission to publish these photographs is gratefully acknowledged."